The Disabled Wife and Mother: Suggested Goals for Family Counselling - Vargo, J. W. (Canadian Journal of Counselling and Psychotherapy, 2012)
The purpose of this article is to provide guidelines for counselling families in which the wife/mother is physically disabled. Common psychological reactions to disability are briefly discussed, followed by four goals of a counselling relationship with a family in which the wife/mother is disabled. These goals include: (1) helping the family accept the disability; (2) helping family members accept their feelings; (3) helping the family understand the psychological factors which affect adjustment; and (4) helping the family redefine the family relationship. It was concluded that once these goals have been achieved, a family with a disabled wife/mother can be treated in the same way as any other family requiring counselling.